Geochemical characteristics of heavy metals concentration in sediments of Quiberon Bay Waters, South Brittany, France - Ong, Meng Chuan; Menier, D.; Shazili, N.A.M.; Yunus, Kamaruzzaman (Oriental Scientific Publishing Co., 2013)
Cr, Co, Cu, Zn, Cd and Pb in the bottom sediments from 93 sites at Quiberon bay were analyzed by Inductively Coupled Plasma Mass Spectrometry (ICPMS) after acid extraction. The ranges of the concentration in the sediments are as follows: 27.3 µg/g (Cr), 11.6 µg/g (Co), 13.8 µg/g (Cu), 42.0 µg/g (Zn), 0.08 µg/g (Cd) and 17.8 µg/g (Pb). Potential contamination of the bay was assessed by Igeo and pollution load index whether the concentration observed represent background or contaminated levels. Based on the results, it can be concluded that the bay is unpolluted for the studied metals.